The Europeanization of Political Parties in Montenegro - Vladimir Vučković (Romanian Journal of European Affairs)
This paper aims to examine the impact of the process of Europeanization on the relevant political parties in Montenegro in the period between the 2009 and 2012 parliamentary elections by focusing on an in-depth content analysis of their election manifestos. The article argues that the EU has demonstrated a limited impact on Montenegrin changes due to the existence of a strong influence of internal factors which hinder the transformative power of the EU. This assertion is particularly observable in the case of the EU impact on Montenegrin parties where the political elite expresses its unwillingness to comply with the EU requirements. The study claims that the influence of Europeanization on domestic changes will be limited in the following period unless the political elite demonstrates true political will to fully align with the EU accession conditions. The research findings may serve as a suitable framework for providing new scientific insights, as well as for the enhancement of current scientific knowledge related to this particular field.